2001
DOI: 10.1002/ajmg.10124
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis, ectopia lentis, and congenital heart defects: Further delineation of an autosomal dominant syndrome with incomplete penetrance

Abstract: The association of craniosynostosis with ectopia lentis is extremely rare. This was recently reported in monozygotic twin sisters, supporting a genetic etiology for this syndromic association. We report on female first cousins once removed who were born with unilateral coronal synostosis. One cousin also had peripheral pulmonic branch stenosis at birth and was later found to have ectopia lentis and severe myopia. The other cousin had an atrial septal defect, mitral valve prolapse, and only mild myopia. Their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
2
Order By: Relevance
“…The disorder has been reviewed by Quercia and Teebi [2002], who reported two cousins: one with craniosynostosis, ectopia lentis, and peripheral pulmonic synostosis, the other with craniosynostosis, atrial septal defect, and mitral valve prolapse, but no ectopia lentis. Cruysberg et al [1999] reported affected monozygotic twin sisters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disorder has been reviewed by Quercia and Teebi [2002], who reported two cousins: one with craniosynostosis, ectopia lentis, and peripheral pulmonic synostosis, the other with craniosynostosis, atrial septal defect, and mitral valve prolapse, but no ectopia lentis. Cruysberg et al [1999] reported affected monozygotic twin sisters.…”
mentioning
confidence: 99%
“…Both autosomal dominant and autosomal recessive modes of inheritance should be considered. The affected cousins of Quercia and Teebi [2002] suggest dominant inheritance with incomplete penetrance; etiologic heterogeneity is also possible since cardiac defects were found in both cousins. The disorder needs to be further delineated.…”
mentioning
confidence: 99%
“…Η βρεφική έκθεση μετά τη γέννηση σε παράγοντες όπως είναι το υδροξείδιο του αργιλίου, μέσω φαρμακευτικών σκευασμάτων μπορεί να οδηγήσουν σε κρανιοστένωση όπως αναφέρθηκε παραπάνω. Το 1995, οι Pivnick et al [479] , [506][507][508][509][510][511][512][513][514][515][516][517][518][519] Πρέπει να γίνει μια σημαντική διάκριση μεταξύ σποραδικών (nonsyndromic) και συνδρομικών κρανιοσυνοστεώσεων. Οι σποραδικές συνοστεώσεις, όπως εξάλλου αναφέρθηκε, γενικά, είναι απομονωμένες, ενώ οι συνδρομικού συνοστεώσεις περιλαμβάνουν μια ποικιλία ανωμαλιών, που συχνά σχετίζεται με το σχηματισμό των άκρων και την ανάπτυξη του προσώπου.…”
Section: ενοχοποιούμενοι παράγοντες κινδύνουunclassified
“…Τα ευρήματα αυτά έχουν νόημα όταν αναλογιστεί κανείς τη γενετική των κρανιοσυνοστεώσεων. [506][507][508][509][510][511][512][513][514][515][516][517][518][519] Τα γονίδια που είναι υπεύθυνα για τις συνδρομικές κρανιοσυνοστεώσεις, που σχετίζονται με τους μοριακούς παράγοντες που εμπλέκονται στη βιολογία των κρανιακών ραφών. Τα μόρια TGF-beta και IGF είναι οι πλέον άφθονοι παράγοντες ανάπτυξης που βρέθηκαν στα οστά.…”
Section: ενοχοποιούμενοι παράγοντες κινδύνουunclassified